Nickel hyperaccumulation in New Caledonian Hybanthus (Violaceae) and occurrence of nickel-rich phloem in Hybanthus austrocaledonicus. (24th June 2020) - Paul, Adrian L D; Gei, Vidiro; Isnard, Sandrine; Fogliani, Bruno; Echevarria, Guillaume; Erskine, Peter D; Jaffré, Tanguy; Munzinger, Jérôme; van der Ent, Antony
Abstract: Background and Aims: Hybanthus austrocaledonicus (Violaceae) is a nickel (Ni) hyperaccumulator endemic to New Caledonia. One of the specimens stored at the local herbarium had a strip of bark with a remarkably green phloem tissue attached to the sheet containing over 4 wt% Ni. This study aimed to collect field samples from the original H. austrocaledonicus locality to confirm the nature of the green 'nickel-rich phloem' in this taxon and to systematically assess the occurrence of Ni hyperaccumulation in H. austrocaledonicus and Hybanthus caledonicus populations. Methods: X-ray fluorescence spectroscopy scanning of all collections of the genus Hybanthus (236 specimens) was undertaken at the Herbarium of New Caledonia to reveal incidences of Ni accumulation in populations of H. austrocaledonicus and H. caledonicus . In parallel, micro-analytical investigations were performed via synchrotron X-ray fluorescence microscopy (XFM) and scanning electron microscopy with X-ray microanalysis (SEM-EDS). Key Results: The extensive scanning demonstrated that Ni hyperaccumulation is not a characteristic common to all populations in the endemic Hybanthus species. Synchrotron XFM revealed that Ni was exclusively concentrated in the epidermal cells of the leaf blade and petiole, conforming with the majority of (tropical) Ni hyperaccumulator plants studied to date. SEM-EDS of freeze-dried and frozen-hydrated samples revealed the presence of dense solid deposits in the phloem bundles that contained >8 wt% nickel. Conclusions: The occurrence of extremely Ni-rich green phloem tissues appears to be a characteristic feature of tropical Ni hyperaccumulator plants.